The importance of casting an eye beyond the dental arch: A case report. (March 2022) - Sweeney, Jill; McCann, Catherine; McLaughlin, Paul
Study models are frequently used in orthodontics and are a key part of both initial assessment and treatment planning. They are an important part of comprehensive orthodontic records; furthermore, study models are an essential diagnostic aid that can be studied in detail without the patient being present. We present a case of a 14-year-old boy with an abnormal palatal swelling detected by his specialist orthodontist after review of study models taken at the initial appointment. At the assessment alone, the significance of the abnormality was not recognised and without the help of study models, diagnosis and treatment of his fibrous dysplasia may have been significantly delayed.